2021
DOI: 10.1016/j.paid.2020.110335
|View full text |Cite
|
Sign up to set email alerts
|

Who wants to reopen the economy during the COVID-19 pandemic? The daring and uncaring

Abstract: Economic shutdowns, which refer to disallowing employees to work on site, are among the most contentious approaches to reduce the spread of COVID-19. While economic shutdowns save lives, their large economic costs have caused some people to develop strong attitudes and even break government-issued mandates, which incurs health risks and often the need to extend the economic shutdowns. In the current article, we argue that the interaction of two personality characteristics, risk-taking tendencies and prosocial … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
17
0
6

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(26 citation statements)
references
References 19 publications
3
17
0
6
Order By: Relevance
“…Do et al (2017) have argued that risk-taking and prosocial tendencies are two inherently intertwined personality dimensions, and that high risk-taking behavior and low social tendency may lead to negate all social protective behaviors. We find evidence of this in the segmentation results, in line with other recent surveys (Howard, 2020).…”
Section: Article Scope and Fit With The Literaturesupporting
confidence: 93%
See 2 more Smart Citations
“…Do et al (2017) have argued that risk-taking and prosocial tendencies are two inherently intertwined personality dimensions, and that high risk-taking behavior and low social tendency may lead to negate all social protective behaviors. We find evidence of this in the segmentation results, in line with other recent surveys (Howard, 2020).…”
Section: Article Scope and Fit With The Literaturesupporting
confidence: 93%
“…Given the segments found, and the importance of risk and social profiling, we now analyze whether those segments may explain differences in NPIs compliance, extending some of the findings by e.g. Howard (2020). Table 5 reports the regression results of linking individual RTC' value to the 10 segments for the three most important actions reported to significantly reduce the reproduction rate of the covid-19 pandemics, that is: social distancing, quarantine, and hygiene (see Bo et al, 2020).…”
Section: Segments As Drivers Of Npismentioning
confidence: 93%
See 1 more Smart Citation
“…Our findings validate what Elgar et al (2020) propose that some dimensions of social capital, such as caring for the community, lead to fewer deaths. Other research found that higher prosocial tendencies were related to an acceptance of making sacrifices such as accepting a temporary economic lockdown (Howard, 2021). While reiterating that cultural values influence how communities react to and behave in this pandemic [see also Seale et al (2020)], our findings indicate that people who care primarily for themselves and have less regard for the consequences of their actions on others behave in ways that are related to personal gain, convenience, and enjoyment, which may increase exposure and risk to the virus.…”
Section: Discussionmentioning
confidence: 99%
“…However, their study also indicated that a younger and unmarried segment with a drinking and smoking habit coming from lower-income households had a reluctant tendency to accord with the recommendations issued by the authorities. Lower engagement in implementing the measures on the COVID-19 were also observed among specific personality traits, among others risk taking traits ( Howard, 2021 ), antisocial risk takers ( Zajenkowski et al, 2020 ), anti-social traits ( Miguel et al, 2020 ), and dark triad trait ( Nowak et al, 2020 ) in various cultural contexts.…”
Section: Introductionmentioning
confidence: 94%